DESIGN AND PERFORMANCE ANALYSIS OF SMART ROOF CLOTHESLINE SYSTEM BASED ON MICROCONTROLLER BY SMARTPHONE APPLICATION - Dewi Rasni Putri; Doan Perdana Perdana; Yoseph Gustommy Bisono (TEKTRIKA, 2017)
Drying clothes is a simple activity to do at home and can not be avoid in daily life. The busyness for each individual outside home makes the activity is not simple anymore. The occurrence of problems such as rain, resulting clothes that have been dry become wet again. To avoid these conditions, the owner needs to be at home when the rain occurs. Smart home is a concept that can be the right and effective solution for every problems in the house. The ability of smart home to control almost all equipment at home make the activities at home efficiently. This Research develop a smart clothes roofing system that can be controlled and monitored by users through an application on smartphone. This system uses rain sensor, humidity and temperature sensors (DHT22), and light sensor (LDR). NRF24L01 as a transceiver module, Arduino Uno as microcontroller and Raspberry Pi as gateway to VPS. The test results obtained the maximum range of NRF2L01 to communicate is 97 meters in LOS (Line of Sight) condition. Distance range of NRF24L01 can also affected the delay and throughput in data transmission process. The availability and reliability of the system are 98.276% and 98.264%.